Cellular Remodelling by Apoptosis During Porcine Placentation. Issue 4 (11th February 2013) - Cristofolini, A; Sanchis, G; Moliva, M; Alonso, L; Chanique, A; Koncurat, M; Merkis, C
Contents The mechanisms that regulate the apoptosis are essential to the normal development and maintenance of homoeostasis and play an important role in placental development in mammals. During porcine pregnancy, there must be a proper cellular remodelling to achieve a normal gestational development. Knowledge of pig physiology during pregnancy will explore options to increase the productivity of this species of high economical value. The purpose of this work was to study the cell morphology and apoptosis of porcine placentas from early, mid and late pregnancy. For that purpose, high‐resolution light microscopy and transmission electron microscopy were performed to the study of cell morphology. TUNEL, the apoptosis index (IAp) and the expression of c‐FLIP through immunohistochemistry technique were used to the study of apoptosis. High‐resolution light microscopy and transmission electron microscopy confirmed the presence of placental cells with ultrastructural apoptotic features. Apoptotic nuclei were detected by TUNEL in different placental structures and phagocytes containing apoptotic bodies. The IAp in villi was 9.34% at early, 0.82% at mid and 23.85% at late pregnancy. Statistically significant differences were found between periods (p < 0.05). In previous studies, we determined a differential induction of the apoptotic routes in the placental villi in agreement with the gestational period. A co‐expression of receptors and mitochondrial proteins in placental connective tissue was detected, but the immunolocalization of c‐FLIP would indicate an endogenous inhibition of the extrinsic pathway. In conclusion, in swine there exists differential activation of inducing apoptotic pathways in different placental structures according to the gestational period.